Development of hardware and software support of computer-integrated technology of complex of secondary condensation of ammonia production - Babichenko, Anatoliy; Lysachenko, Ihor; Kravchenko, Yana; Babichenko, Juliya; Krasnikov, Igor; Shutynskyi, Oleksii (Technology audit and production reserves, 2022)
The object of research is the technological complex of secondary condensation (TCSC) and the control system of a typical ammonia synthesis unit of the AM-1360 series. The analysis of the conditions of its functioning and hardware and technological design was carried out. The coordinates of the control vector are determined. The features of the proposed functional diagram and the necessary algorithmic software for the computer-integrated control technology of the TCSC with a correction subsystem for decision-making under uncertainty are established. The implementation of the proposed solutions is complicated by the use of the information and control complex TDC-300 (USA) with closed-type software installed on the existing ammonia synthesis units. The need for such a control complex to implement a decision-making subsystem under conditions of uncertainty is shown to supplement the existing control system with hardware and software of an «open» type. A computer-integrated TCSC technology based on a three-level hierarchical structure has been created. The implementation of the zero and first levels of such a structure form single software and hardware complex consisting of a programmable logic controller and an automated operator’s workplace based on an industrial computer with installed software. A software implementation of decision-making on the correction of the coordinates of the control vector by additional hardware and software based on the VIPA logic controller and the Zenon SCADA system was made. A scheme of network information flows has been implemented, which illustrates the functioning of the decision-making correction subsystem in the general structure of the TCSC computer-integrated control technology. Implementation of the developed system allows, under the existing uncertainties, to reduce the secondary condensation temperature by an average of 3 °C, which ensures an annual reduction in natural gas consumption by 1 million nm3. The proposed approach to the possibility of combining «open» and «closed» type hardware and software can be applied in other industries.